2023
DOI: 10.1002/jts.22906
|View full text |Cite
|
Sign up to set email alerts
|

The impact of trauma‐focused psychotherapy for posttraumatic stress disorder on interpersonal functioning: A systematic review and meta‐analysis of randomized clinical trials

Abstract: Interpersonal functioning is a common concern for people with postttraumatic stress disorder (PTSD) but is not a key target of most trauma‐focused psychotherapies (TFPs). We preregistered and undertook a systematic review and meta‐analysis of randomized clinical trials (RCTs) examining the efficacy of TFPs for improving interpersonal functioning. Studies were identified through the PTSD Trials Standardized Data Repository, scholarly databases, and the solicitation of unpublished data from the PTSD research com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…To this end, a more comprehensive definition of treatment response is encouraged in future reviews (e.g., specific functional impairment outcomes) such that the true burden of this condition is more appropriately captured. This need is underscored by recent evidence which suggests that T-F psychotherapy may confer moderate gains in a range of functioning factors (Bonfils et al, 2022; Swerdlow et al, 2023), highlighting a need for more focused attention to functional outcomes of treatment rather than focusing only on symptom reduction. Sixth, trials that combined T-F and non-T-F conditions in observed predictor analyses were excluded as our research question focused on the role of predictors of T-F psychotherapy.…”
Section: Limitationsmentioning
confidence: 99%
“…To this end, a more comprehensive definition of treatment response is encouraged in future reviews (e.g., specific functional impairment outcomes) such that the true burden of this condition is more appropriately captured. This need is underscored by recent evidence which suggests that T-F psychotherapy may confer moderate gains in a range of functioning factors (Bonfils et al, 2022; Swerdlow et al, 2023), highlighting a need for more focused attention to functional outcomes of treatment rather than focusing only on symptom reduction. Sixth, trials that combined T-F and non-T-F conditions in observed predictor analyses were excluded as our research question focused on the role of predictors of T-F psychotherapy.…”
Section: Limitationsmentioning
confidence: 99%
“…A limitation of the studies presented here is an overreliance on particular types of dyads: The study samples overwhelmingly included male veterans or SMs and their female civilian romantic partners, and participants were overwhelmingly White. Important exceptions to this general rule include the meta‐analysis by Swerdlow and colleagues (2023), which took a broader measure of changes in interpersonal functioning rather than limiting their analysis to romantic relationships; the Lewis et al. (2023) sample, which consisted of civilians rather than military personnel; and the Howard et al.…”
mentioning
confidence: 99%
“…These difficulties are an important and potentially modifiable intergenerational pathway through which parental trauma and psychopathology lead to negative child outcomes (Castro-Vale et al, 2020; Leen-Feldner et al, 2013; Roberts et al, 2012). Interpersonal difficulties appear to be reciprocally related to PTSD symptoms over time and can persist even when PTSD symptoms decrease (Lord et al, 2020; Swerdlow et al, 2023). This suggests a need for targeted and trauma-informed interventions to address interpersonal difficulties.…”
mentioning
confidence: 99%